AN EXPERIMENTAL STUDY OF INFLUENCE PORTFOLIO DIVERSIFICATION ON INVESTMENT STRATEGIES IN IRAQI E-SERVICE FINANCIAL COMPANIES - Lect. Ziad Najim Abed (Scholars Digest Publishing, 2024)
This experimental study examines the impact of portfolio diversification on investment strategies in Iraqi e-service financial companies, highlighting its role as a fundamental step in achieving high-risk-adjusted returns. Portfolio diversification involves combining assets moving in opposing directions, reducing unsystematic risk. The study explores the relationship between investment strategies and portfolio diversification, emphasizing how diversification influences various strategies. The study comprehensively explains how diversification enhances investment strategies by analyzing portfolio diversification theory. It underscores its role in improving risk management and balancing risk and return. Using empirical studies and diverse sources, the research demonstrates that diversification is not merely an additional option but a core component of building effective investment strategies, especially within Iraq's challenging economic environment. The findings reveal a positive relationship between portfolio diversification and investment strategies. Diversification contributes to stabilizing returns and minimizing unsystematic risks, thus enabling companies to navigate economic fluctuations better. Consequently, the research recommends adopting diversification as an integral element of investment planning for Iraqi e-service financial companies to ensure sustainability and investment stability. In conclusion, the study highlights the positive impact of diversification on enhancing investment performance in the Iraqi context, affirming its necessity as a central aspect of investment policies and strategies to address challenges and achieve growth objectives.